Effect of tocopherol supplementation during last trimester of pregnancy on mRNA abundances of interleukins and angiogenesis in ovine placenta and uterus - Kasimanickam Ramanathan K; Kasimanickam Vanmathy R; Haldorson Gary J; Tibary Ahmed (BMC, 2012)
Abstract Background Interleukins (IL) play an important role in angiogenesis. Tocopherol possesses immunomodulating effect in addition to antioxidant property. The objective of this study was to determine whether gamma tocopherol's (gT) angiogenic activity in placental network is enhanced via promoting interleukins. Methods Pregnant ewes (N = 18) were supplemented, orally, with 500 mg of alpha tocopherol (aT; N = 6) or 1,000 mg of gT (N = 7) or placebo (CON; N = 5) once daily from 107 to 137 days post breeding. Uterine and placental tissue samples were obtained at the end of supplementation to evaluate relative mRNA expressions of IL-1b, IL-6, IL-8, Tumor Necrosis Factor (TNF) alpha, Vascular Endothelial Growth Factor (VEGF), kinase insert domain receptor (KDR; VGFR2; a type III receptor tyrosine kinase), and soluble fms-like tyrosine kniase-1 (sFlt1 or sVEGFR1) in uterus, caruncle and cotyledon. Results Oral supplementation of gT increased IL-6, IL-8, KDR and VEGF mRNA abundances whereas sFlt1 mRNA abundance was suppressed in uterus, caruncle and cotyledon, compared to aT and placebo treated ewes (P < 0.05). The TNF alpha and IL-1b mRNA abundances were suppressed in uterus, caruncle and cotyledon but TNF alpha is higher in gT group compared to aT group (P < 0.05), whereas IL-1b was similar between treatment groups (P > 0.1). Conclusions Gamma tocopherol supplementation increased IL-6, IL-8, and KDR mRNA abundances and suppressed sFlt1 and TNFalpha mRNA abundances thereby increased VEGF mRNA expression and angiogenesis in placental vascular network during late gestation. It is plausible that the angiogenic effect of gamma tocopherol in placental vascular network is exerted via an alternate path by enhancing IL-6 and IL-8.